Kepak Garuda: Penyebaran Inspirasi Lewat Wallpaper Tokoh Inspiratif - Widhyatmoko, Danu (Bina Nusantara University, 2013)
Kepak Garuda (www.kepakgaruda.com) conducts their social activities by distributing free desktop wallpapers which are full of inspirational figures through new media internet and online social media based. Article begins with a background activity conducted by Kepak Garuda. Research method used is literature study, continued by reflective data analysis. It can be summed up that there are more comprehensive pictures of the benefit gained as a result of activities undertaken by Kepak Garuda.